Problematika Peraturan Pengganti Undang-Undang Nomor 1 Tahun 2017 tentang Organisasi Masyarakat - Ismail, Rezki Robiatul Aisyiah (Faculty of Law, Mulawarman University, 2019)
Indonesia is a democratic constitutional state set forth in article 1 paragraph (3) of the 1945 Constitution of the State of the Republic of Indonesia, as a legal state for running a state and protection of human rights under the law. One of them is in Article 28 E Paragraph (3) of the 1945 Constitution of the State of the Republic of Indonesia which states that everyone has the right to freedom of association, assembly, and expression. The regulation concerning the Organization of the Community is in fact set out in Law No. 17 of 2013 on Community Organizations. Community organization is an organization founded and formed by the community voluntarily based on the similarity of aspirations, wills, needs, interests, activities and objectives to participate in development in order to achieve the objectives of the Unitary State of the Republic of Indonesia based on Pancasila. Community organizations may be in the form of two, incorporated and non-legal entities. The Government issued a Regulation in Lieu of Law of the Republic of Indonesia Number 2 Year 2017 on the amendment to Law No. 17 of 2013 on Social Organization and then with the Regulation of Lieu of the Law the government made a policy that the Government in this case gave authority to the Ministry of Justice and Human Rights Asasi Manusia dissolved social organization which contradict with principle of Pancasila one of them is Hizbut Tahrir Indonesia discussion Government Regulation of society organization still has weakness substantially. Government regulation in lieu of laws of community organizations in order to reinforce the principle of contrarius actus is not appropriate because it has actually attached to government officials without the need to be affirmed in the legislation.